Comparison of Efficacy of Single Dose Tranexamic Acid versus Placebo before Surgery in Females Undergoing Surgery for Ovarian Cancer - Naz, Sadia; Zahoor, Sadia (Indus Journal of Bioscience Research, 2025)
Objective: To compare the efficacy of single-dose tranexamic acid versus placebo in reducing transfusion requirements and perioperative blood loss in females undergoing surgery for ovarian cancer. Methods: This randomized controlled trial was conducted in the Department of Obstetrics and Gynecology, Sheikh Zayed Hospital and Medical College, Rahim Yar Khan, over a 6-month period (December 2024 to May 2025). A total of 372 women aged 18–60 years with ovarian cancer of FIGO stage I–III and ASA class I–III were enrolled and randomized into two groups. Group A (n=186) received tranexamic acid 15 mg/kg intravenously before surgery, while Group B (n=186) received placebo. The primary outcome was efficacy, defined as no postoperative transfusion requirement. Results: All 372 patients completed the study. Baseline characteristics were comparable between groups (p >0.05). The requirement for transfusion was significantly lower in the tranexamic acid group (29.6%) compared to placebo (44.1%) (p=0.003). Efficacy was achieved in 70.4% of patients in the tranexamic acid group versus 55.9% in the placebo group (p=0.003). Mean perioperative blood loss was markedly reduced in the tranexamic acid group (548.3 ± 198.7 ml) compared to placebo (692.1 ± 242.6 ml) (p